Evaluation of the immune feature of ACPA-negative rheumatoid arthritis and the clinical value of matrix metalloproteinase-3 - Liang, Zhaojun; Wang, Nan; Shang, Lili; Wang, Yanlin; Feng, Min; Liu, Guangying; Gao, Chong; Luo, Jing (Frontiers in Immunology, 2022)
Anti-citrullinated protein antibodies (ACPAs) are highly specific for the diagnosis of rheumatoid arthritis (RA). However, about one-third of RA patients are negative for ACPAs, which presents a challenge to the early diagnosis of RA. The purpose of this study was to analyze differences in lymphocyte subsets and CD4+ T cell subsets between ACPA+ and ACPA- RA patients, and to evaluate the value of matrix metalloproteinase-3 (MMP-3) as a diagnostic and monitoring marker in ACA- RA patients. A total of 145 ACPA+ RA patients, 145 ACPA- RA patients, and 38 healthy controls (HCs) were included in this study. Peripheral lymphocyte subsets were detected using flow cytometry, and serum MMP-3 was detected using chemiluminescence. Information about joint symptoms, other organ involvement, and related inflammatory markers was also collected. The results showed that, compared to ACPA- RA patients, ACPA+ cases had greater imbalances between peripheral CD4+ T cell subsets, mainly manifested as an increase in T-helper 1 (Th1) cells (p < 0.001) and decrease in regulatory T (Treg) cells (p = 0.029). This makes these patients more prone to inflammatory reactions and joint erosion. MMP-3 levels in ACPA+ and ACPA- RA patients were significantly higher than in HCs (p < 0.001), and MMP-3 could effectively distinguish between ACPA- RA patients and HCs (area under the curve [AUC] = 0.930, sensitivity 84.14%, specificity 92.11%). MMP-3 was also a serum marker for distinguishing between RA patients with low and high disease activities. Further analysis showed that MMP-3 was positively correlated with the levels of inflammatory markers and disease activity, and negatively correlated with the levels of lymphocyte subsets. In addition, with improvements in the disease, MMP-3 levels decreased, and further increased as the patients started to deteriorate. In summary, our research showed that there was a mild imbalance between peripheral CD4+ T cell subsets in ACPA- RA patients. MMP-3 may be used as a potential marker for early diagnosis of ACPA- RA. MMP-3 was an important index for RA disease evaluation, disease activity stratification, and prognosis.